“Broad” consent, exceptions to consent and the question of using biological samples for research purposes different from the initial collection purpose - Petrini, Carlo (Social science & medicine (1982), 2010)
An important ethical issue regarding biological samples stored in biobanks is unforeseen future sample use, when no or limited subject consent is obtained. Biobanks of biological samples have significant future research potential, but may cause conflicts of interest regarding the consent obtained. Indeed, ethics, deontology, and jurisprudence generally advise that consent must be specific and circumstantiated. However, it is not possible to foresee all of the future circumstances in which the samples might be useful, nor is it possible to re-contact all subjects in order to gain consent for a new use. The main arguments for the use of “broad” consent are presented with a brief discussion of the conditions where it may be legitimate not to obtain consent. Particular attention is given to the expressed positions of national and international bioethics bodies.